Carotid intima media thickness in older children and adolescents with HIV taking antiretroviral therapy. Issue 17 (April 2020) - Majonga, Edith D.; Chiesa, Scott T.; McHugh, Grace; Mujuru, Hilda; Nathoo, Kusum; Odland, Jon Oyvind; Kaski, Juan Pablo; Ferrand, Rashida A.
Abstract : Abstract: Increased carotid intima-media thickness (cIMT) is reported in both adults and children with human immunodeficiency virus (HIV) in high income settings and is associated with an increased risk of cardiovascular disease, but data from sub-Saharan Africa is lacking. We assessed cIMT using ultrasound in perinatally HIV-infected children aged 6 to 16 years taking antiretroviral therapy (ART) for ≥6 months compared with HIV-uninfected controls in Harare, Zimbabwe. Groups were compared using unpaired t test and potential predictors of cIMT were assessed using multiple linear regression. A total of 117 participants with HIV, of whom 55 (45%) were female and 75 healthy uninfected controls were included. Participants with HIV were younger than uninfected controls, 10.7 (2.4) years versus 11.9 (2.6) years ( P  = .001). Mean cIMT was 0.40 (0.05) mm in those with HIV versus 0.40 (0.04) mm in healthy controls ( P  = .377). There was no association between cluster of differentiation 4 count, HIV viral load, and duration on ART and cIMT. Children with HIV taking ART have similar cIMT to uninfected children. Increasing numbers of children with HIV are reaching adulthood and longitudinal studies to assess the effect of long-term HIV and ART on vascular changes are required.